Comparative Sociology, 1950-1963. A Trend Report and Bibliography by Robert M. Marsch; Current Sociology. La Sociologie Contemporaine. Vol. XIV, núm. 2 - Uribe Villegas, Óscar (Revista Mexicana de Sociología, 2020)
No disponible.